The study of stress and work-life balance program at bi technologies corporation sdn bhd on cognitive ergonomics functions to improve work performance - Kamarulzaman, Mahmad Khairai (2022)
The judgement of human in industry is difficult to eliminate because there are various types of tasks that need human as a main source of performance. Cognitive functions of employees are positively related to stress level, body and mind condition to operate the production line. This study attempts to address the stress problem among operators also a study on Heart Rate Variability (HRV) coherence ratio performance, Work-Life Balance (WLB) and worker's productivity. The main objective of this study is to develop a Work-Life Balance (WLB) module and to study it effectiveness in employee's productivity performance. The Work-Life Balance (WLB) module developed comprises of Heart Rate Variability (HRV) training, personal management, work management, and spiritual enrichment checklist. A group of employees were selected based on the Depression Anxiety Stress Scale (DASS) score for intervention sessions, 36 from total 319 employees with high score and low score were divided into Treatment Group and Control Group. The Work-Life Balance (WLB) module was used to monitor the HRV score, Satisfaction With Life Scale (SWLS), and productivity of employees in production area. The Work-Life Balance (WLB) module was used for employees to reduce stress while providing information to promote a Work-Life Balance (WLB) environment. The selected employees' performances are measured after eight intervention sessions in a 2 month period. Every 2 weeks they will have a session to strengthen the Work-Life Balance (WLB) module implementation. The result shows that employees in the Treatment Group are able to increase HRV coherence ratio score from the mean value of 0.67 to 1.28, reducing stress level from the mean value of 45.9 to 29.1, improve Satisfaction With Life Scale(SWLB) score from the mean value of 5.57 to 6.26 and increase worker's productivity by comparing pre and post-condition. From this study, all employees that were selected for intervention session showed improvement in terms of employee productivity by an average of 10% in overall plant performance in production area. As employees improve their cognitive ergonomics function on post intervention sessions, visual mechanical inspection workstation showed the highest productivity improvement with an average of 13%. The results indicate that the Work-Life Balance (WLB) module can be used in an electronics industry company to improve work performance as well as increasing the wellness level among factory employees.